HUBUNGAN PENGGUNAAN KONTRASEPSI SUNTIKAN 3 BULAN TERHADAP DISFUNGSI SEKSUAL - Restu Arahman Melba; Sri Utami; Siti Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Sexual dysfunction is the presence of a disorder in one or more aspects of sexual function were assessedincluding sexual desire/libido, orgasm, and pain. This research aims to know the relationship of the use ofcontraceptive injections 3 months to sexual dysfunction. This research is descriptive correlation design byused cross sectional approach. The research was conduct  at Clinics Tempuling Sub-district. The number ofsamples is 38 respondents who are willing to be the respondent, according to the criteria of inclusion anduse of the technique of accidental sampling. Instrument used questionnaire. Analysis of univariate analysis isused to find out the bivariat analysis and frequency distribution using the chi-square test. The respondentssexual dysfunction occur with long term usage > 2 years is by 28 people (71.8%). The result of study showedthat there is a significant correlation the use of contraceptive injections 3 months to sexual dysfunction withp value (0.01). It is concluded that the use of contraceptive injections 3 months can lead to sexualdysfunction side effects to the acceptors injections 3 months. The results of this research can be used as oneof the reference for health promotion of counseling or education about 3 months injection contraceptiveeffect sexual dysfunction.Keywords: sexual dysfunction, contraceptive, 3 months injection.